The neurotrophin receptor, gp75, forms a complex with the receptor tyrosine kinase TrkA (The Rockefeller University Press, 1996)
The high-affinity NGF receptor is thought to be a complex of two receptors , gp75 and the tyrosine kinase TrkA, but direct biochemical evidence for such an association had been lacking. In this report, we demonstrate the existence of such a gp75-TrkA complex by a copatching technique. Gp75 on the surface of intact cells is patched with an anti- gp75 antibody and fluorescent secondary antibody, the cells are then fixed to prevent further antibody-induced redistributions, and the distribution of TrkA is probed with and anti-TrkA antibody and fluorescent secondary antibody. We utilize a baculovirus-insect cell expression of wild-type and mutated NGF receptors. TrkA and gp75 copatch in both the absence and presence of NGF. The association is specific, since gp75 does not copatch with other tyrosine kinase receptors, including TrkB, platelet-derived growth factor receptor- beta, and Torso (Tor). To determine which domains of TrkA are required for copatching, we used a series of TrkA-Tor chimeric receptors and show that the extracellular domain of TrkA is sufficient for copatching with gp75. A chimeric receptor with TrkA transmembrane and intracellular domains show partial copatching with gp75. Deletion of the intracellular domain of gp75 decreases but does not eliminate copatching. A point mutation which inactivates the TrkA kinase has no effect on copatching, indicating that this enzymatic activity is not required for association with gp75. Hence, although interactions between the gp75 and TrkA extracellular domains are sufficient for complex formation, interactions involving other receptor domains also play a role.